2010
DOI: 10.1111/j.1365-2109.2010.02690.x
|View full text |Cite
|
Sign up to set email alerts
|

Feeding high inclusion of whole grain white lupin (Lupinus albus) to rainbow trout (Oncorhynchus mykiss): effects on growth, nutrient digestibility, liver and intestine histology and muscle fatty acid composition

Abstract: The e¡ect of dietary inclusion of whole grain white lupin (Lupinus albus) on growth performance, histology, muscle fatty acid composition and nutrient digestibility was investigated in an 11-week growth and a 4-week digestibility trial with rainbow trout (initial body weight of 54.0 AE 6.2 and 181.9 AE 3.4 g respectively). Four experimental extruded diets were formulated to contain 0%, 30%, 40% and 50% of whole grain lupin and fed to triplicate groups of ¢sh twice a day until apparent satiation. Faeces were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
24
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 44 publications
(96 reference statements)
9
24
1
Order By: Relevance
“…The body biochemical composition does not change with increasing dietary inclusion of plant sources, for instance lupin insertion (Lupinus albus) in the diet of rainbow trout (Bórquez et al 2011). In our beluga, the level of whole-body moisture was significantly higher in fish fed 15-25 % of FBM compared to that in other groups.…”
Section: Body Compositionmentioning
confidence: 81%
See 1 more Smart Citation
“…The body biochemical composition does not change with increasing dietary inclusion of plant sources, for instance lupin insertion (Lupinus albus) in the diet of rainbow trout (Bórquez et al 2011). In our beluga, the level of whole-body moisture was significantly higher in fish fed 15-25 % of FBM compared to that in other groups.…”
Section: Body Compositionmentioning
confidence: 81%
“…The majority of the previous studies reported in fish nutrition have mainly focused on the possibility of partial or full replacements of fish meal diets with alternative plant protein sources (Kaushik et al 1995;Francis et al 2001). Among the plant sources such as beans, lupins, and peas (commonly known legumes), legumes are promising ingredients due to the relatively high protein and energy contents, and have been successfully assayed in different species of fish (Burel et al 2000;Farhangi and Carter 2001;Gaber 2006;Azaza et al 2009;Adamidou et al 2011;Bórquez et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that dietary inclusion of both leaf meals did not result in some of the intestine abnormalities that have been reported in carnivorous fish fed plant diets. These include a decrease in basophil granulocytes, and distal displacement of enterocyte nucleus (Borquez et al, 2011). Other authors have reported a widening of the central stroma within the mucosal folding, higher amounts of connective tissue; and an infiltration of inflammatory cells in the lamina propria (Krogdahl et al, 2000;Refstie et al, 2000).…”
Section: Discussionmentioning
confidence: 91%
“…The use of white lupin (Lupinus albus L.) seed meal as a feed ingredient in diets for salmonid fish has been previously assessed with variable outcomes (Bórquez, Hernández, et al 2011;Borquez, Serrano, et al 2011;Omnes et al Forthcoming 2015). Studies suggest that the occurrence of anti-nutritional factors in lupin seeds can significantly diminish the nutritive value of this ingredient (Burel et al 2000;Peterson 2000;Farhangi and Carter 2001;Glencross et al 2008;Erbas 2010;Serrano et al 2012).…”
Section: Introductionmentioning
confidence: 99%